A comparative study of offensive strategies in LFIPT Futsal Super League 2023 / Nur Fatihiliana Idris ... [et al.]. - Idris, Nur Fatihiliana; Raja Hussain, Raja Nurul Jannat; Mohamed, Muhamad Noor; Saiful Annur, Muhamad Safiq; Mazaulan, Mardiana; Adnan, Mohd Aizzat; Abu Kassim, Nurul Ain; Shari, Maisarah; Md Radzi, Noor Azila Azreen (Universiti Teknologi MARA, Negeri Sembilan, 2025)
Futsal is a fast-paced sport in which offensive tactics play a crucial role in determining match outcomes. Strategies such as positional play and high pressing significantly enhance goal-scoring opportunities, setting winning teams apart. This study expands the existing futsal literature, providing valuable insights for coaches [1]. Effective tactics create scoring chances, losing possession can shift control to the opposing team, making recovery challenging for the attackers [2].